2016
DOI: 10.1016/j.biopha.2016.04.030
|View full text |Cite
|
Sign up to set email alerts
|

Long-term exercise training as a modulator of mammary cancer vascularization

Abstract: Background: Breast cancer remains a leading cause of death by cancer worldwide. It is commonly accepted that angiogenesis and the expression of angiogenic factors such as vascular endothelial growth factor-A (VEGF-A) is associated with the increased risk of metastasis and poor patient outcome.Objective: This work aimed to evaluate the effects of long-term exercise training on the growth and vascularization of mammary tumors in a rat model. Materials and methods:Fifty female Sprague-Dawley rats were divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
46
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(53 citation statements)
references
References 62 publications
6
46
0
Order By: Relevance
“…The vascularization of the mammary tumors used in this study was previously evaluated by thermography, US (power Doppler and B‐flow modes), and immunohistochemistry using vascular endothelial growth factor A immunoexpression and quantification of microvessel density. Data from all techniques suggested higher vascularization of mammary tumors in the MNU exercised group compared with mammary tumors in the MNU sedentary one …”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…The vascularization of the mammary tumors used in this study was previously evaluated by thermography, US (power Doppler and B‐flow modes), and immunohistochemistry using vascular endothelial growth factor A immunoexpression and quantification of microvessel density. Data from all techniques suggested higher vascularization of mammary tumors in the MNU exercised group compared with mammary tumors in the MNU sedentary one …”
Section: Discussionmentioning
confidence: 89%
“…Data from all techniques suggested higher vascularization of mammary tumors in the MNU exercised group compared with mammary tumors in the MNU sedentary one. 19,20 Although immunohistochemistry and microvessel density analysis are considered reference standards for assessment of tumor vascularization, they are invasive techniques that can be performed only after excision of tumors and do not allow an evaluation of angiogenesis at different times throughout an experimental protocol. 25 Additionally, immunohistochemistry is not reproducible (because of distinct laboratory conditions, antibodies, and antigen retrieval), and the evaluation is relatively subjective, 2-dimensional, and not necessarily representative of vascularity throughout the entire sample.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Malicka et al demonstrated that moderate intensity training reduced the number of induced tumors in rats (4). Other studies showed that in animals physically active at puberty (rodent treadmill, tunnels and ladders), the risk of developing the disease is decreased, the possible tumor development is delayed and smaller-sized tumors are observed (5)(6)(7)(8)(9)(10)(11). Currently, a longer survival time is observed in individuals after cancer treatment who regularly exercise (12)(13)(14)(15)(16)(17) (23,24).…”
mentioning
confidence: 99%